Dust survey following the final shutdown of TEXTOR: metal particles and fuel retention. (22nd January 2016) - Fortuna-Zaleśna, E; Weckmann, A; Grzonka, J; Rubel, M; Esser, H G; Freisinger, M; Kreter, A; Sergienko, G; Ström, P
Abstract: The work presents results of a broad TEXTOR dust survey in terms of its composition, structure, distribution and fuel content. The dust particles were collected after final shutdown of TEXTOR in December 2013. Fuel retention, as determined by thermal desorption, varied significantly, even by two orders of magnitude, dependent on the dust location in the machine. Dust structure was examined by means of scanning electron microscopy combined with energy-dispersive x-ray spectroscopy, focused ion beam and scanning transmission electron microscopy. Several categories of dust have been identified. Carbon-based stratified and granular deposits were dominating, but the emphasis in studies was on metal dust. They were found in the form of small particles, small spheres, flakes and splashes which formed 'comet'-like structures, clearly indicating directional effects in the impact on surfaces of plasma-facing components. Nickel-rich alloys from the Inconel liner and iron-based ones from various diagnostic holders were the main components of metal-containing dust, but also molybdenum and tungsten debris were detected. Their origin is discussed.